1998
DOI: 10.1002/(sici)1099-1085(199801)12:1<105::aid-hyp566>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal reorganization of subglacial drainage inferred from measurements in boreholes

Abstract: Abstract:The eect of the formation of a major subglacial drainage channel on the behaviour of the subglacial drainage system of Haut Glacier d'Arolla, Switzerland, was investigated using measurements of borehole water level and the electrical conductivity and turbidity of basal meltwaters. Electrical conductivity pro®les were also measured within borehole water columns to identify the water sources driving water level changes, and to determine patterns of water circulation in boreholes. Prior to channel format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 20 publications
4
32
0
Order By: Relevance
“…Similar behaviour, with nearby boreholes displaying dissimilar but diurnally varying pressures, has been recorded at a number of other glaciers (e.g. Gordon et al, 1998;Fudge et al, 2005Fudge et al, , 2008.…”
Section: Phasesupporting
confidence: 74%
“…Similar behaviour, with nearby boreholes displaying dissimilar but diurnally varying pressures, has been recorded at a number of other glaciers (e.g. Gordon et al, 1998;Fudge et al, 2005Fudge et al, , 2008.…”
Section: Phasesupporting
confidence: 74%
“…As for the end-ofwinter configuration, the IDS water head is more sensitive to the leakage length scale than is the EPL length. Gordon et al (1998) 70 m at the opening of the efficient drainage system, in good agreement with the modelled drop for leakage length scale ϕ ≥ 10 m. Figure 10 compares the modelled EPL extent for ϕ = 10 and ϕ = 20 m to the reconstructed channel system at the end of the 1990 melt season (Sharp et al, 1993). This comparison shows a good agreement between the extent of the modelled active EPL and the channel system observed at the end of summer for both values of ϕ.…”
Section: Transient Summer Configurationsupporting
confidence: 66%
“…Their results suggest that the moulins directly fed an efficient channelised component of the drainage system while the boreholes, by contrast, monitored a hydraulically inefficient drainage system. This juxtaposition of efficient subglacial channels draining waters between hydraulically inefficient areas of the bed mimics conditions observed in alpine glacial systems [59,68]. A contrary conclusion was reached by a study which found minimal subglacial water pressure variations in a borehole 34 km from the ice margin, under ice~830 m thick [69], which the authors interpreted as indicative of a lack of channelised drainage extending inland beneath deep ice.…”
Section: Subglacial Meltwater Processesmentioning
confidence: 82%